CT characteristics and clinical implications of acute type A aortic intramural hematoma - Yen, Hsu-Ting; Wu, Chia-Chen; Lee, Yi-Wei; Lo, Chien-Ming; Chen, Yen-Yu (Frontiers in Cardiovascular Medicine, 2023)
Objectives: Computed tomography (CT) has been increasingly used in the diagnosis of acute aortic syndrome, and a number of high-risk CT imaging features have been reported. We aimed to identify CT imaging findings suggesting high-risk for acute aortic syndrome by examining clinical outcomes of patients with acute type A aortic intramural hematoma (TAIMH). Methods: This retrospective study analyzed the relationship of clinical patient characteristics and imaging features with mortality and aortic events in 63 patients receiving initial medical treatment for TAIMH. Multivariate regression analysis was used to determine the predictors of aortic events, and the Kaplan–Meier method was used to analyze survival and aortic events. Results: During a median follow-up of 4.2 years, 25 patients experienced aortic events and 40% of these occurred within 7 days of admission. In total, 12 patients experienced aortic death and 12 patients underwent open aortic surgery or endovascular stenting for aortic disease. In multivariate regression analysis, penetrating atherosclerotic ulcers (PAUs) or ulcer-like projections (ULPs) (P = 0.04) and pericardial effusion (P = 0.03) were independent predictors of aortic events. In the Cox regression model, PAUs/ULPs (P = 0.04) and pericardial effusion (P = 0.04) were independently associated with lower aortic event-free survival. Conclusions: Identification of high-risk CT features is important for clinical decision-making during TAIMH treatment. Early and frequent CT imaging follow-up is required in patients receiving medical treatment. PAUs/ULP and pericardial effusion were the strongest predictors of adverse aortic events.